2016
DOI: 10.1155/2016/9387651
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deposition Condition on Y2O3Coatings Produced by Pulsed Electrophoretic Deposition

Abstract: Y2O3nanoparticle suspension aqueous solution was prepared using citric acid. Then, Y2O3film was deposited using this solution with pulsed electrophoretic deposition (EPD). A dense Y2O3film of 25.7 μm thickness was obtained with deposition conditions of 0.5 wt% Y2O3concentration, bias voltage of 0.5 V, and bias frequency of 1 kHz. The respective resistivities of the as-deposited film and films heat-treated at 200°C and 400°C were 2.84 × 103 Ω·cm, 5.36 × 104 Ω·cm, and 2.05 × 106 Ω·cm. A 59.8 μm thick dense Y2O3f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Miyazaki and his colleagues placed Y 2 O 3 NPs films using the pulsed EPD technique. 29 It was found that the best deposition conditions for this approach include employing a low concentration of yttrium nanoparticles in the presence of low pressure and high frequency. When the concentration of Y 2 O 3 NPs in a solution was raised, the thickness of the film was considerably decreased.…”
Section: Yttrium Oxides Nps As Anticorrosionmentioning
confidence: 99%
“…Miyazaki and his colleagues placed Y 2 O 3 NPs films using the pulsed EPD technique. 29 It was found that the best deposition conditions for this approach include employing a low concentration of yttrium nanoparticles in the presence of low pressure and high frequency. When the concentration of Y 2 O 3 NPs in a solution was raised, the thickness of the film was considerably decreased.…”
Section: Yttrium Oxides Nps As Anticorrosionmentioning
confidence: 99%
“…6),7) A Si 2 N 2 O radiative cooling device can thus be formed easily using the abovementioned Si 2 N 2 O particles with the pulsed EPD method. 6), 7) In the present investigation, we synthesized Si 2 N 2 O particles using the previously reported method, 5) and fabricated radiative cooling devices with Si 2 N 2 O coatings on metal Al plates using Si 2 N 2 O nano-particle with a pulsed EPD. Furthermore, we evaluated the radiative cooling ability of the obtained devices.…”
Section: Introductionmentioning
confidence: 99%